Influence of fashionable mukhlisan lahuddin vision and mission statements in a construction company in Malaysia - Shorbani, Syakina Zahra; Keleşoğlu, Osman; Mhd. Sarif, Suhaimi (IIUM Press, International Islamic University Malaysia, 2020)
This study explores the influence of fashionable mukhlisan lahuddin vision and mission statements in a construction company in Malaysia. Mukhlisan provides the direction or path for a company to become and to perform in the business it is doing. Lahuddin creates the way of life or corporate culture for the company to operate its business. By having fashionable or adjustable to the contemporary needs of the company, it will reenergize the company to be more competitive and performing.